PENGGUNAAN APLIKASI FLIP DALAM BERTRANSAKSI ANTAR BANK - Nurul Atmaningrum (2021)
In 2015, Flip was founded as a pioneer application that provides free interbank money transfer services. Flip is present due to the anxiety of the founders when they had to make interbank transfers with admin fees set by the bank. During the COVID-19 pandemic, many people are trying to minimize their expenses, and one way to do so is by saving on transaction costs. Flip can be a solution for those who want to reduce their expenses, by saving transaction fees while sending money between banks. It is also supported by the fact that users of Flip have increased twofold after the pandemic, compared to before the pandemic. The research also proves that Flip provides convenience for users and Flip becoming their main choice for interbank money transfer transactions.